2021
DOI: 10.32702/2307-2105-2021.9.72
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Methods and Models in the Management of Current Assets of an Industrial Enterprise

Abstract: Метою даної роботи є теоретичне обґрунтування аспектів застосування математичних методів та моделей в системі управління оборотними активами промислового підприємства та напрямків підвищення ефективності управління оборотними активами. Стаття присвячена узагальненню теоретичних аспектів щодо визначення сутності поняття «управління оборотними активами підприємства» та оцінки процесу управління ними на основі математичних методів та моделей. Обґрунтовано необхідність та важливість ефективного управління оборотни… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…It was concluded that the solvency of the business entity, the level of its profitability, the formation of work opportunities in unforeseen situations, the scale and level of production and final sale of products will depend on the quality of management of current assets. Колодзієв [2], І. Єпіфанова [2], І. Тарасенко [7], І. Цуркан [8], В. Чобіток [9],…”
mentioning
confidence: 99%
“…It was concluded that the solvency of the business entity, the level of its profitability, the formation of work opportunities in unforeseen situations, the scale and level of production and final sale of products will depend on the quality of management of current assets. Колодзієв [2], І. Єпіфанова [2], І. Тарасенко [7], І. Цуркан [8], В. Чобіток [9],…”
mentioning
confidence: 99%